Respuesta :
Answer:
[tex]\displaystyle x = 3 \pm i\sqrt{3}[/tex]
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Algebra I
- Factoring
- Standard Form: ax² + bx + c = 0
- Quadratic Formula: [tex]\displaystyle x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}[/tex]
Algebra II
- Imaginary Numbers: √-1 = i
Step-by-step explanation:
Step 1: Define
x² - 6x + 12 = 0
Step 2: Identify Variables
Compare the quadratic to standard form.
x² - 6x + 12 = 0 ↔ ax² + bx + c = 0
a = 1, b = -6, c = 12
Step 3: Find Roots
- Substitute in variables [Quadratic Formula]: [tex]\displaystyle x=\frac{-(-6)\pm\sqrt{(-6)^2-4(1)(12)}}{2(1)}[/tex]
- [Quadratic Formula] Simplify: [tex]\displaystyle x=\frac{6\pm\sqrt{(-6)^2-4(1)(12)}}{2(1)}[/tex]
- [Quadratic Formula] [√Radical] Evaluate exponents: [tex]\displaystyle x=\frac{6\pm\sqrt{36-4(1)(12)}}{2(1)}[/tex]
- [Quadratic Formula] [√Radical] Multiply: [tex]\displaystyle x=\frac{6\pm\sqrt{36-48}}{2(1)}[/tex]
- [Quadratic Formula] [√Radical] Subtract: [tex]\displaystyle x=\frac{6\pm\sqrt{-12}}{2(1)}[/tex]
- [Quadratic Formula] [√Radical] Factor: [tex]\displaystyle x=\frac{6\pm \sqrt{-1} \cdot \sqrt{12}}{2(1)}[/tex]
- [Quadratic Formula] [√Radicals] Simplify: [tex]\displaystyle x=\frac{6 \pm 2i\sqrt{3}}{2(1)}[/tex]
- [Quadratic Formula] [Fraction - Denominator] Multiply: [tex]\displaystyle x=\frac{6 \pm 2i\sqrt{3}}{2}[/tex]
- [Quadratic Formula] [Fraction - Numerator] Factor: [tex]\displaystyle x=\frac{2(3 \pm i\sqrt{3})}{2}[/tex]
- [Quadratic Formula] [Fraction] Divide: [tex]\displaystyle x = 3 \pm i\sqrt{3}[/tex]